1992
DOI: 10.1042/bj2850647
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of R- and S-1,3-butanediol in perfused livers from meal-fed and starved rats

Abstract: The metabolism of millimolar concentrations of R- or S-1,3-butanediol has been studied in perfused livers from fed and starved rats. Protocols were designed to measure in the same experiment (i) uptake of the diol, (ii) the contribution of the diol to ketogenesis, (iii) the contribution of the diol to total fatty acid plus sterol synthesis, and (iv) conversion of S-1,3-butanediol into S-3-hydroxybutyrate. Our data show that R- and S-1,3-butanediol are taken up by the liver at the same rate. Most of the metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 21 publications
0
41
0
Order By: Relevance
“…The ketone supplements tested in this study allowed for a rapid and controlled induction of physiologic ketosis without the need for fasting or severe dietary restrictions. Previous studies have demonstrated the use of exogenous ketones as a means to induce a dose-dependent hyperketonemia (1–7 mM) in rats, mice, dogs, pigs and humans (Desrochers et al, 1992, 1995; Ciraolo et al, 1995; Brunengraber, 1997; Puchowicz et al, 2000; Clarke et al, 2012; Srivastava et al, 2012). Exogenous ketogenic supplementation mimics the metabolic and physiologic effects of the KD, including enhancing mitochondrial biogenesis, anaplerosis, suppression of glycolysis and increasing ATP and adenosine production, all thought to mediate the therapeutic effects of KD in epilepsy (Veech, 2004; Srivastava et al, 2012; Kesl et al, 2014; Poff et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The ketone supplements tested in this study allowed for a rapid and controlled induction of physiologic ketosis without the need for fasting or severe dietary restrictions. Previous studies have demonstrated the use of exogenous ketones as a means to induce a dose-dependent hyperketonemia (1–7 mM) in rats, mice, dogs, pigs and humans (Desrochers et al, 1992, 1995; Ciraolo et al, 1995; Brunengraber, 1997; Puchowicz et al, 2000; Clarke et al, 2012; Srivastava et al, 2012). Exogenous ketogenic supplementation mimics the metabolic and physiologic effects of the KD, including enhancing mitochondrial biogenesis, anaplerosis, suppression of glycolysis and increasing ATP and adenosine production, all thought to mediate the therapeutic effects of KD in epilepsy (Veech, 2004; Srivastava et al, 2012; Kesl et al, 2014; Poff et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Among potential precursor molecules, 1,3-butanediol and 1,3-butanediol acetoacetate esters have been most extensively studied. These compounds are metabolized in a chain of enzymatic reactions in the plasma and liver to the same ketone bodies that are produced during the ketogenic diet (Desrochers et al, 1992(Desrochers et al, , 1995Ciraolo et al, 1995). Although each of the aforementioned alternatives is still early in development, the idea of developing the ketogenic diet in a 'pill' is very attractive and may be approachable.…”
Section: Discussionmentioning
confidence: 99%
“…Ketone bodies themselves have short half-lives, and ingestion or infusion of sodium βOHB salt to achieve therapeutic ketosis provokes an untoward sodium load. R/S-1,3-butanediol is a non-toxic dialcohol that is readily oxidized in the liver to yield d/l -βOHB (Desrochers et al, 1992). In distinct experimental contexts, this dose has been administered daily to mice or rats for as long as seven weeks, yielding circulating βOHB concentrations of up to 5 mM within 2 h of administration, which is stable for at least an additional 3h (D'Agostino et al, 2013).…”
Section: Therapeutic Application Of Ketogenic Diet and Exogenous Ketomentioning
confidence: 99%